Mental disorders diagnosed in childhood and at‐risk mental state in a help‐seeking population. Issue 2 (4th July 2012) - Comparelli, Anna; Pucci, Daniela; Savoja, Valeria; Kotzalidis, Giorgio D.; Falcone, Ilaria; Angelone, Massimiliano; Comazzetto, Claudia; Emili, Emanuele; Rigucci, Silvia; Tatarelli, Roberto; Girardi, Paolo
Abstract: Aim: Disorders usually first diagnosed in infancy, childhood or adolescence (DUFD‐ICA) may have preceded the onset of psychosis by several years and share some co‐morbidity with psychotic disorders, but only a few studies have investigated this aspect. We looked for past or current DUFD‐ICA in a sample of first adult psychiatric service users assessed for the presence of an at‐risk mental state with the Structured Interview for Psychosis‐risk Syndromes (SIPS). Methods: We interviewed with the SIPS 159 first‐time help seekers (age range 13–30 years) at adult psychiatric services who volunteered to participate in the study. For psychiatric diagnoses, we used the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition‐Text Revision . We also assessed retrospectively the presence of DUFD‐ICA and administered the Brief Psychiatric Rating Scale (BPRS) and the Global Assessment of Functioning. The sample has been subdivided diagnostically into first‐episode psychosis, multiple episode psychosis, ultra‐high risk (UHR) and other diagnoses. Results: The risk for having one of first‐episode psychosis, multiple episode psychosis or UHR was over 3.45 higher in the DUFD‐ICA‐positive history group than in the non‐DUFD‐ICA. Grouping the UHR with the not full‐blown psychosis cases resulted in a further increase of the risk to 4.71. DUFD‐ICA‐positive participants scored higher than non‐DUFD‐ICA on the Positive, Negative and Disorganization scales of the SIPS and on several core‐psychotic BPRS items. Conclusions: A positive history of DUFD‐ICA increases the risk of a diagnosis of prodromal or current psychosis at help seeking. Impaired neurodevelopment may be shared among the psychoses and DUFD‐ICA.